Analisis Letak Cooling Pad Kandang Close House Ayam Broiler Terhadap Performa Dan Pendapatan Peternak Anitasari Farm Di Kecamatan Dampit Kabupaten Malang - Shidiq Bahrum Muchith; Muhammad Saikhu; Dewi Ratih Ayu Daning (Jurnal Ragam Pengabdian, 2026)
This study analyzed the effect of cooling pad placement in closed-house broiler cages on production performance and farmer income at Anitasari Farm, Dampit District, Malang Regency. The research compared two ventilation systems, namely front cooling pad and side cooling pad configurations, during one production cycle of 38 days. A descriptive quantitative approach was applied using direct observation, interviews, and farm documentation. Primary data included final body weight, feed conversion ratio, mortality, performance index, temperature, humidity, ammonia concentration, wind speed, production costs, and farmer revenue. Data analysis employed descriptive statistics and an independent t-test to identify differences between both systems. The results indicated that cooling pad placement influenced microclimate distribution inside the house and affected broiler productivity. The side cooling pad system produced more stable temperature and humidity conditions, improved feed efficiency, reduced heat stress, and supported better broiler performance. These conditions contributed to higher production efficiency and increased farmer income compared with the front cooling pad system. The study concludes that appropriate cooling pad placement is essential for optimizing environmental control, broiler productivity, and economic profitability in tropical closed-house poultry farming systems. The findings support recommendations for sustainable poultry management.